Psychological Contracts and Employee Health - Jacqueline A.-M. Coyle-Shapiro; Costa, S.; Chang, C. (Handbook on Management and Employment Practices, 2022)
The primary thrust of psychological contract (PC) research has focused on employees’ outward directed responses when they experience contract breach and violation. These responses have been primarily directed at the organization as the source of the psychological contract breach. In doing so, the inward-focused consequences of breach on employees’ health have been relegated to the side- lines. We place the spotlight on the health consequences of psychological con- tracts and, in particular, employees’ experience of contract breach and violation. In this chapter, we begin with a brief review of the conceptualization of psycho- logical contracts and examine the theoretical links between psychological con- tracts and health. We present the emerging empirical evidence on the deleterious effects of breach and violation on employee health. We review potential moder- ators that may strengthen or weaken the effects of contract breach/violation on health. Given that contract breach occurs regularly, how do individuals cope post- breach and what are the effects on their health? Finally, we outline a number of avenues for future research to advance knowledge on the relationship between psychological contracts and employee health.